2019
DOI: 10.1021/acsnano.9b07063
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Microtube Aerogel Derived from Kapok Fiber: An Efficient and Recyclable Sorbent for Oils and Organic Solvents

Abstract: A carbon microtube aerogel (CMA) with hydrophobicity, strong adsorption capacity, and superb recyclability was obtained by a feasible approach with economical raw material, such as kapok fiber. The CMA possesses a great adsorption capacity of 78–348 times its weight. Attributed to its outstanding thermal stability and excellent mechanical properties, the CMA can be used for many cycles of distillation, squeezing, and combustion without degradation, which suggests a potential practical application in oil–water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 69 publications
(98 reference statements)
1
60
0
Order By: Relevance
“…It has been reported that a high specific surface area is beneficial for the improvement of adsorption performance. 45 Therefore, we selected the 3D MoS 2 -PVP aerogel (20 mg cm À3 ) with a high specific surface area as the research object. The 3D MoS 2 -PVP aerogel can stand stably on the surface of a flower ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that a high specific surface area is beneficial for the improvement of adsorption performance. 45 Therefore, we selected the 3D MoS 2 -PVP aerogel (20 mg cm À3 ) with a high specific surface area as the research object. The 3D MoS 2 -PVP aerogel can stand stably on the surface of a flower ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The 3D MoS 2 -PVP aerogel was prepared by the freeze-drying method. 45,[75][76][77][78] Briefly, MoS 2 powder was uniformly dispersed in PVP solutions (1 mg cm À3 ) under stirring and the concentration of MoS 2 was set to 5, 10, 15 and 20 mg cm À3 , respectively. Then the suspension was poured into a rubber mold placed at the top of a cold steel rod, which was cooled by adding liquid nitrogen and kept at À70 1C for 1 h. Then the obtained frozen sample was further freeze-dried by using a Labconco-195 freeze-drier for 72 h. Finally, the 3D MoS 2 -PVP aerogel was obtained.…”
Section: Preparation Of the 3d Mos 2 -Pvp Aerogelmentioning
confidence: 99%
See 1 more Smart Citation
“…Oil-water mixtures generated from daily life and industrial production have caused not only serious environmental pollution, but also the waste of treasured resources. [1][2][3] Moreover, tiny amounts of water in fuel can condense on the metal surface of an engine to produce corrosion, which greatly shorten its service-lifetime and increase the risk of engine failure. [4][5][6] Therefore, separation of oil/water mixtures has drawn growing interests of scientists and engineers all over the world.…”
Section: Introductionmentioning
confidence: 99%
“…Porous adsorption materials with both hydrophobicity and oleophilicity are powerful and renewable for the remediation of oil spills, which can be used to collect the crude oil in situ from the ocean surface or the oil/water mixtures without negative consequence to the environment. Major areas of interest involve the designation, preparation, and evaluation of various porous materials including sponges, [9][10][11] hydrogels, [12][13][14] aerogels, [15][16][17] and membranes. [18][19][20] Typically, the porous materials must be endowed with low surface energy via the decoration or modification by hydrophobic chemicals.…”
mentioning
confidence: 99%